Quality of publicly available information on the principles and methods of first aid in cardiac arrest: a structured analysis of Russian-language web resources - A. A. Birkun; G. V. Ivanova (Российский кардиологический журнал, 2024)
Aim. The high availability of modern information and communication technologies, including the Internet, social networks and mobile devices, creates unique opportunities for widely informing people about the importance, principles and methods of first aid in cardiac arrest. The aim was to assess the completeness and correctness of recommendations for first aid in cardiac arrest presented in open Russian-language web resources.Material and methods. In February 2024, Yandex and Google searched for publicly available web pages in Russian that provided information on principles and methods of first aid in cardiac arrest in adults. The content of the web pages was analyzed using the ERC Research NET checklist for assessing the quality of educational resources on basic cardiopulmonary resuscitation (CPR). Additionally, we determined whether web pages contained unnecessary recommendations.Results. The sample for analysis consisted of 27 unique web pages. An assessment of information quality provided on them showed poor coverage of key internationally recommended principles and methods for first aid in cardiac arrest. In particular, 81,5% of web pages (n=22) did not report on the importance of initiating chest compressions as early as possible, 85,2% (n=23) did not report on the need to minimize pauses in compressions, 37,0% (n=10) and 25,9% (n=7) did not report on the recommended depth and frequency of compressions, respectively, and 22,2% (n=6) did not report on the need to call an ambulance immediately after recognizing cardiac arrest. Only 33,3% (n=9) of resources mentioned the possibility of compression-only CPR by people who do not have artificial respiration skills. In addition, 77,8% of web pages (n=21) contained redundant instructions that contradicted current international recommendations on CPR, and 29,6% of resources (n=8) allowed actions or inactions that clearly threatened the safety of the victim when bystanders provided first aid to cardiac arrest.Conclusion. The quality of publicly available Russian-language web resources on first aid in cardiac arrest is generally unsatisfactory. Open access to low-quality resources creates a risk of many people developing false ideas and making mistakes by bystanders in real emergency situations. There is a need to establish uniform procedures for systematic monitoring and quality assurance of publicly available information explaining the principles and methods of first aid in cardiac arrest.